The gaits of marsupials and the evolution of diagonal‐sequence walking in primates. Issue 2 (24th November 2019) - Cartmill, Matt; Brown, Kaye; Atkinson, Christopher; Cartmill, Erica A.; Findley, Erica; Gonzalez‐Socoloske, Daniel; Hartstone‐Rose, Adam; Mueller, Joanne
Abstract: Objectives: Documenting the variety of quadrupedal walking gaits in a variety of marsupials (arboreal vs. terrestrial, with and without grasping hind feet), to aid in developing and refining a general theory of gait evolution in primates. Materials and Methods: Video records of koalas, ringtail possums, tree kangaroos, sugar gliders, squirrel gliders, wombats, numbats, quolls, a thylacine, and an opossum walking on a variety of substrates were made and analyzed to derive duty factors and diagonalities for symmetrical walking gaits. The resulting distributions of data points were compared with published data and theories. Results: Terrestrial marsupials' gaits overwhelmingly plot slightly below the theoretical "horse line" (Cartmill et al., Zoological Journal of the Linnean Society. 2002;136:401–420) typical of terrestrial mammals; arboreal marsupials' gaits overwhelmingly plot more decisively above it. Both distributions are roughly parallel to the horse line, but arboreal animals exhibit increased diagonality, so that their higher‐speed walking gaits overlap with those of typical primates on the Hildebrand diagram of diagonality against duty factor. Conclusions: Quadrupeds avoid gaits lying exactly on the (theoretically optimum) horse line, to avoid fore/hind limb interference ("forging"). This can be accomplished by either a slight reduction in diagonality ("downshifting") or a more decisive increase ("upshifting"). Tree‐dwellers adopt the second option to eliminate unilateral bipods of support from the gait cycle. The upshifted horse line represents an early phase in the evolution of primate‐like diagonal‐sequence gaits.